Education necessity for veterinary-producer relationship creation and sustainability: a mixed method study - Ritter, Nicola L.; Gonzales, Molly; Mays, Glennon (Frontiers in Veterinary Science, 2025)
ObjectivesTo identify barriers to veterinarian-producer partnerships and suggest collaborative applied education as a means to enhance economic efficiency and sustainability of small and medium livestock operations and rural veterinary practices.Materials and methodsA participatory needs assessment, exploring the willingness and barriers to producer-veterinarian partnerships to enhance small/medium livestock operations, was distributed to Texas producers and veterinarians. Quantitative and qualitative data were collected via online, closed-ended survey questions and free response interviews. Responses were analyzed using SPSS and HyperRESEARCH to identify relevant terms, ideas, patterns, or themes.ResultsSimilar responses from 115 veterinarians and 58 producers revealed five major themes regarding relationship barriers: time, financial challenges, communication, competing perspectives, and respect. Overall producers reported greater willingness to partner in all areas, health care (90%), to achieve goals (80%), and to expand business (70%), than veterinarians. Veterinarian interviews revealed a need for increased animal health education among producers, while more than 60% of producers expressed high interest in continuing education on animal health topics.DiscussionVeterinarians and producers experience similar barriers to establishing partnerships. Both groups also recognize a need for education and prefer in-person collaborative learning communities Such educational opportunities can encourage formal veterinary-producer partnerships and provide solutions that enhance the economic efficiency and sustainability of small/medium livestock operations.